THEORETICAL JUSTIFICATION OF SYSTEM OF ANTI-RECESSIONARY FINANCIAL CONTROLLING AT THE ENTERPRISE - N. Danilochkina; M. Bobrova; V. Proskuryakov (Вестник университета)
In article it is considered concepts of anti-crisis financial controlling as one most progressive modern methods of management at the domestic enterprises. The detailed analysis of a concept controlling is carried out, considerable attention is paid to definition of his purposes and tasks, stages of formation of work of department of controlling and identification of his main functions. It is shown that financial controlling as the system of information support is directed to coordination of all subsystems of business management in the conditions of the unstable economic environment.